1995
DOI: 10.1111/j.1751-1097.1995.tb05250.x
|View full text |Cite
|
Sign up to set email alerts
|

INACTIVATION OF CELL SURFACE RECEPTORS BY PHEOPHORBIDE a, A GREEN PIGMENT ISOLATED FROM Psychotria acuminata

Abstract: The inhibition of cytokine and monoclonal antibody binding cell surfaces caused by an extract of Psychotria acuminata, a medicinal plant used in the traditional medicine of the people of Belize (Central Africa), was attributed to the presence of pheophorbide a and pyropheophorbide a. Since the binding of tumor necrosis factor-alpha, interleukin-8, complement factor 5a as well as epidermal growth factor to target cells was dramatically reduced, the inhibition was not receptor or cytokine specific. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…This is inconsistent with the inactivation of cell surface receptors induced by a photodynamic process in other studies [7,13,42]. Moreover, our results showed that HPD alone or in association with laser irradiation increased EGF receptor expression of C6 cells.…”
Section: Influence Of Hpd and Laser Irradiation On Egf Receptor Exprecontrasting
confidence: 81%
“…This is inconsistent with the inactivation of cell surface receptors induced by a photodynamic process in other studies [7,13,42]. Moreover, our results showed that HPD alone or in association with laser irradiation increased EGF receptor expression of C6 cells.…”
Section: Influence Of Hpd and Laser Irradiation On Egf Receptor Exprecontrasting
confidence: 81%
“…Whereas the molecular mechanism by which PPME promotes IL-1 receptor internalization is unknown, it could be interesting to determine whether this effect is restricted to receptors that do not require homo-or heterodimerization for their functioning. A modification of cell-surface receptor by PPME photosensitization has recently been published (62); curiously, these authors reported that a mixture between pheorbide-a and PPME can reduce binding of cytokines to their receptors (TNF-␣, IL-8, complement factor 5a, and epidermal growth factor). As these data were obtained (i) by measuring cytokine binding to their receptor on neutrophils and (ii) with a mixture of photosensitizers, they reinforce the idea that these compounds can interact with cell-surface receptors and either inactivate them or trigger transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although, to date, little is known about the photosensitising agents present in different phytoplankton species (Oda et al 2001, Sato et al 2002, several such agents have been found in animal and plant sources (Kimura and Takahashi 1981, Glinski et al 1995, Matroule et al 1999. : Absorption spectrum of the purified haemolytic toxin and the cytotoxicity against HeLa cells at irradiances of various wavelengths.…”
Section: Resultsmentioning
confidence: 99%